Low temperature thermal expansion of fullerite C60 alloyed with argon and neon - Aleksandrovskii, A. N.; Gavrilko, V. G.; Esel`son, V. B.; Manzhelii, V. G.; Udovidchenko, B. G.; Maletskiy, V. P.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The linear thermal expansion of compacted fullerite C60 alloyed with argon (ArxC60) and neon (NexC60) are investigated by a dilatometric method. The experimental temperature is 2-12 K. In the same temperature interval the thermal expansion of ArxC60 and NexC60 are examined after partial desaturationof the gases from fullerite. It is found that Ar and Ne alloying affects the temperature dependence of thethermal expansion coefficient of C60 quite appreciably. The libration and translation contributions to the thermal expansion of pure C60 are separated. The experimental results on the thermal expansion are used to obtain the Debye temperature of pure C60. The effects observed are tentatively interpreted.